Perbandingan Kepuasan Pelanggan Terhadap 3 Brand Makanan Kekinian di Medan - Angela Heyneker; Alvin Caesar; Eko Nakata; Jerycho Taivin; Vanness Wilson Sutantio (Politeknik Kampar, 2024)
Analysis of customer satisfaction of three Chicken Preset brands, namely Prambanan, Cobek, and Surabaya, showed that Prambanaan was the best in meeting customer expectations. Cobek was, although not as good as Prambana, still offering a satisfactory experience with attractive menu variations, competitive prices, and good service. On the other hand, Surabaya showed a lower level of satisfaction, probably due to a lack of competitive appeal. This analysis demonstrates the importance of factors such as menu variation, price, and service in influencing customer satisfaction, providing important perspectives for improving customer experience in the food industry.